2016
DOI: 10.18632/oncotarget.9999
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1291 targets the FOXA2-AGR2 pathway to suppress pancreatic cancer cell proliferation and tumorigenesis

Abstract: Pancreatic cancer is the fourth leading cause of cancer death in the United States. Better understanding of pancreatic cancer biology may help identify new oncotargets towards more effective therapies. This study investigated the mechanistic actions of microRNA-1291 (miR-1291) in the suppression of pancreatic tumorigenesis. Our data showed that miR-1291 was downregulated in a set of clinical pancreatic carcinoma specimens and human pancreatic cancer cell lines. Restoration of miR-1291 expression inhibited panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 64 publications
(80 reference statements)
10
47
0
Order By: Relevance
“…Our recent studies have demonstrated that miR-1291 suppresses proliferation and tumorigenesis of PC cells [17]. To further delineate the molecular mechanisms through which miR-1291 controls PC cell growth, computational analysis was conducted to predict potential targets of miR-1291.…”
Section: Arid3b Is a Direct Target Of Mir-1291mentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent studies have demonstrated that miR-1291 suppresses proliferation and tumorigenesis of PC cells [17]. To further delineate the molecular mechanisms through which miR-1291 controls PC cell growth, computational analysis was conducted to predict potential targets of miR-1291.…”
Section: Arid3b Is a Direct Target Of Mir-1291mentioning
confidence: 99%
“…Furthermore, multiple miRNAs display tissue -specific aberrant expression in cancer development, suggesting the potential of developing miRNA based anticancer therapies besides serving as diagnostic or prognostic markers [12,13] including those for PC [14][15][16]. Recently, we have identified that miR-1291 is significantly downregulated in PC tissues compared with normal pancreatic tissues [17]. Our studies have also demonstrated that restoration of miR-1291 expression/function suppresses the proliferation, migration, invasion, and tumorigenesis of PC cells through the induction of apoptosis and cell cycle arrest, as well as alteration of PC cell metabolome [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxa2 is a member of the fork head transcription factor family which is widely involved in the regulation of cell proliferation and differentiation26, 27. Prior studies have showed that Foxa2 may be abnormally expressed in a number of cancers, which sequently lead to the development of tumors24, 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have showed that Foxa2 may be abnormally expressed in a number of cancers, which sequently lead to the development of tumors24, 28, 29. A number of miRNAs have been shown to be able to regulate Foxa2 expression such as miR-1291, miR-29 and miR-124a27, 30, 31. But the potential relationship of miR-200a targeting Foxa2 in human hepatocellular carcinoma have not been studied before.…”
Section: Discussionmentioning
confidence: 99%